Properties of particleboard from juvenile acacia mangium at 800kg/m3 with 7%, 9% and 11% resins / Mohd Ridzuan Samsury - Samsury, Mohd Ridzuan (2005)
Particleboard is one of the many types of product based on wood. The research that has been done is to produce particleboard from Juvenile Acacia mangium wood dusts which were mixed with three level of resin urea-formaldehyde and these were 7%, 9% and 11%. This mixture should be cured by heat and pressure. The properties of this particleboard will be determined be the several types of test including bending test, thickness swelling, and water absorption.